(untitled) (Comprehensive Journal of Science, 2026)
Given the importance of using presentations to easily convey ideas and solidify information in all fields of knowledge, including history, which is often viewed as a narrative discipline concerned solely with the past and not keeping pace with developments, particularly in the technological field, this research aims to highlight the importance of using digital methods alongside the historical narrative approach in studying and narrating human events and activities. It is generally accepted that documents and images become historical records after a certain period of time. This study aims to demonstrate how to benefit from preserving presentations prepared for academic activities (seminars, conferences, research, lectures, and lessons) by documenting them to create an archive that can be utilized in the future. It emphasizes the necessity of preserving history and connecting it to the present and future while maintaining authenticity and identity.